Light LED PANEL - Mona Hasan Amer; Esraa Mahmood Nassar (My University, 2013)
The project is  a LED Light Panel . The LED Light Panel is an 8x8 array of individually-controllable RGB LEDs encased in a high quality acrylic enclosure. It can stream content from a PC via USB . The LEDs are pixelized and diffused with a custom insert making for a nice glowing square pixel rather than a bright washed out point source . An Arduino-compatible microcontroller is used to interface the LEDs to a PC and is fully programmable via a standard USB cable . It can  be used  in  Club / Music venue , Dorm rooms , Living room coffee tables and  Basement wall dcor .   It provide a study of pixels ,each photo is pixelized then transfer through USB to be show in the panel ,we Will add additional stuff  to it to be able to control the led using the sensors or add  sound effects to the LEDs to light depending on the music .